Life-history traits and geographical divergence in wild rice (Oryza rufipogon) gene pool in Indochina Peninsula region - T. Pusadee (2018)
© 2015 Association of Applied Biologists. Indochina Peninsula is the primary centre of diversity of rice and lies partly in the centre of origin of cultivated rice (Oryza sativa) where the wild ancestor (Oryza rufipogon) is still abundant. The wild gene pool is potentially endangered by urbanisation and the expansion of agriculture, and by introgression hybridisation with locally cultivated rice varieties. To determine genetic diversity and structure of the wild rice of the region we genotyped nearly 1000 individuals using 20 microsatellite loci. We found ecological differentiation in 48 populations, distinguishable by their life-history traits and the country of origin. Geographical divergence was suggested by isolation of the perennial Myanmar populations from those of Cambodia, Laos and Thailand. The annual types would be most likely to have lost genetic variation because of genetic drift and inbreeding. The growing of cultivated and wild rice together, however, gives ample opportunities for hybridisation, which already shows signs of genetic mixing, and will ultimately lead to replacement of the original wild rice gene pool. For conservation we suggest that wild rice should be conserved ex situ in order to prevent introgression from cultivated rice, along with in situ conservation in individual countries for the recurrent evolutionary process through local adaptation, but with sufficient isolation from cultivated rice fields to preserve genetic integrity of the wild populations.